Japanese quail farming: Novelty through Bamboo shelter house technology - Singh, Sanjay Kumar; Kumar, Pankaj; Pandey, Sheshdhar; Kumar, Anjani (Indian Farming, 2022)
The residents of east Champaran district of northern Bihar are fond of meat of chicks and quail. Champaran meat (syn. Handi meat) is unequivocally equivalent to geographical indication (GI) of this region, however people are now preferring meat of japanese quail (syn. Bater in vernacular language) especially during winter (rabi) season as fried or with curry. Due to high mortality of young chicks during winter season and threat of predatory animals, many landless women farmers were previously reluctant to adopt quail farming. Now, low cost bamboo shelter house (each cost of `1,500–2,000) is available in Bihar and more than 25 women farmers have adopted this novel quail farming technique which has ensured women empowerment, livelihood and nutritional security in Chakia and Mehsi block of east Champaran, Bihar.